WareBot: A Flexible Autonomous Robot for Smart Warehouse Management in Small and Medium-Sized Enterprises - Alhroub, Osama; Warasna, Issa; Rjoub, Ismail (My University, 2026)
This project introduces Warebot, a multi-robot autonomous system designed to support small and medium enterprises in achieving daily warehouse operations without modifying the existing infrastructure. The need for this project arises from several problems that directly affect warehouses. Many existing solutions are highly dependent on the warehouse environment, which leads to challenges such as requiring large modifications. This increases the cost of changes and may force the environment to be closed during upgrades. Our system addresses these problems by removing infrastructure-related dependencies and shifting the work to the robots’ software, with minimal reliance on the warehouse infrastructure. Our system is deployed on Neobotix MP-400 robots equipped with advanced features and sensors such as LiDAR and IMU to sense, recognize, localize, and navigate the environment. By using SLAM (Simultaneous Localization and Mapping) with a single robot, we can create a global map that is later shared among all robots. Warehouse operations are controlled through Multi-Robot Task Allocation (MRTA) and priority matrices based on battery level, robot location, and robot status. This makes the system efficient in utilizing robot software and fast in completing warehouse operations. While robots are moving, they use global path planning that continues to run and is updated using the A* algorithm to ensure the robots can be aware of changes in the environment, such as moved shelves or new obstacles that appear suddenly. This enables robots to adapt to changes, generate new paths, and successfully reach their destinations. Obstacle avoidance is managed by the Dynamic Window Approach (DWA), which enables real-time obstacle avoidance. To face multi-robot challenges, our system implements smart techniques such as robot awareness and cooperative perception. These techniques allow robots to detect each other and treat other robots as dynamic obstacles, making each robot adapt its movements correctly based on what is on the shared map. When conflicts or deadlocks occur, the robots can solve that using continuous replanning with obstacle avoidance, which generates new path planning during movement. These ensure good coordination between robots on the same map. Communication between the robots and the server is performed using lightweight MQTT protocols, enabling low-latency data exchange within an acceptable time. Additionally, Warebot has a web interface that allows workers to track, monitor, and control the overall system. WareBot presents a strong solution since it works in a wide range of environments and adapts to any changes, and is scalable when the number of robots increases. All these techniques and algorithms that are implemented in our system make it flexible and effective for managing daily warehouse operations. يقدّم هذا المشروع نظامًا ذكيًا متعدد الروبوتات باسم WareBot، يهدف إلى أتمتة عمليات المستودعات دون الحاجة إلى إجراء أي تعديلات على البنية التحتية الحالية. تنبع أهمية هذا العمل من التحديات التي تواجه أنظمة المستودعات التقليدية، والتي غالبًا ما تعتمد بشكل كبير على البيئة المحيطة، مما يؤدي إلى الحاجة لتعديلات كبيرة وتكاليف مرتفعة وتعطيل العمليات التشغيلية. يعالج نظام WareBot هذه الإشكاليات من خلال توفير نظام أكثر مرونة وقابلية للتوسع يعتمد بشكل أساسي على البرمجيات الذكية. يعتمد النظام على روبوتات Neobotix MP-400 المزودة بمستشعرات الليدار (LiDAR) ووحدات القياس بالقصور الذاتي (IMU)، مما يتيح للروبوتات إدراك البيئة المحيطة، وتحديد موقعها، والتنقل ذاتيًا. يستخدم النظام خوارزمية SLAM لإنشاء خريطة عالمية للمستودع يتم مشاركتها مع جميع الروبوتات. يتم التحكم في مهام الروبوتات باستخدام نظام تخصيص المهام متعدد الروبوتات (MRTA)، مع الاعتماد على مصفوفات الأولوية بناءً على مستوى البطارية، وموقع الروبوت، وحالته، مما يحسن كفاءة التنفيذ وتوزيع المهام. أثناء حركة الروبوتات، يتم تخطيط المسارات عالميًا باستخدام خوارزمية A*، بينما يتم تفادي العوائق باستخدام خوارزمية النافذة الديناميكية (DWA). ولمعالجة تحديات التفاعل بين الروبوتات، يعتمد النظام على مبدأ الوعي المتبادل بين الروبوتات (Robot awareness) والإدراك التعاوني، حيث يستطيع كل روبوت اكتشاف الروبوتات الأخرى واعتبارها عوائق ديناميكية، ويتم تكييف الحركة بشكل آني وفقًا لما هو موجود على الخريطة المشتركة. كما يتم حل حالات التعارض والانسداد (Deadlock) من خلال إعادة التخطيط المستمر (Continuous Replanning) مع تجنب العوائق ديناميكيًا، مما يساهم في تحسين التنسيق بين الروبوتات داخل البيئة المشتركة. يتم التواصل بين الروبوتات والخادم المركزي عبر بروتوكول MQTT خفيف الوزن، مما يضمن تبادل بيانات منخفض التأخير وموثوقًا. كما تم الاعتماد بنية حوسبية هجينة (الحافة-السحابة) لتحقيق توازن بين سرعة المعالجة المحلية ومرونة التخزين السحابي، ويوفر واجهة ويب تفاعلية للمشغلين تتيح حالة الروبوتات، وتخصيص المهام، ومراقبة أداء النظام في الزمن الحقيقي. يُعتبر نظام WareBot حلاً مرنًا وقابلًا للتوسع ليتناسب مع بيئات تشغيل متعددة وأعداد مختلفة من الروبوتات، مع الحفاظ على الأداء والاستقرار. ومن خلال الدمج بين التحكم المركزي، والتخطيط الذكي، وإعادة التخطيط المستمر، والتواصل المرن، يقدم النظام منصة متكاملة لإدارة المستودعات ذاتية التشغيل بكفاءة عالية.
Number Of Pages : 98 , Department of Computer Engineering
Keywords: Autonomous Robots; Warehouse Automation; SLAM Navigation; MQTT; BOT